Effect of a distant rigid wall on microstreaming generated by an acoustically driven gas bubble. (21st February 2014) - Doinikov, Alexander A.; Bouakaz, Ayache
Abstract: A theory is developed that describes acoustic microstreaming around a gas bubble undergoing small radial and translational oscillations in the presence of a distant rigid wall. It is shown that the presence of the wall can change the amplitude and the phase of the bubble oscillations in such a way that the intensity of acoustic microstreaming is increased considerably as compared with that generated by the same bubble in an infinite liquid. This occurs if the driving frequency is close to the resonance frequency that the bubble has in the presence of the wall. Equations for acoustic microstreaming in the boundary layer at the wall are also provided.